2013
DOI: 10.3390/nu5083099
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Dietary Fiber Sources in Companion Animal Nutrition

Abstract: The US has a pet population of approximately 70 million dogs and 74 million cats. Humans have developed a strong emotional bond with companion animals. As a consequence, pet owners seek ways to improve health, quality of life and longevity of their pets. Advances in canine and feline nutrition have contributed to improved longevity and well-being. Dietary fibers have gained renewed interest in the pet food industry, due to their important role in affecting laxation and stool quality. More recently, because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
64
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 80 publications
1
64
0
1
Order By: Relevance
“…In addition it has been found that fibers in combination with proteins help regulate satiety levels in dogs [2]. Furthermore, fibers may help regulate the digestive process and the glycemic response in dogs and cats [3,4]. Depending on the fiber type and consumed amount, different effects on nutrient digestibility and fecal formation can be promoted [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition it has been found that fibers in combination with proteins help regulate satiety levels in dogs [2]. Furthermore, fibers may help regulate the digestive process and the glycemic response in dogs and cats [3,4]. Depending on the fiber type and consumed amount, different effects on nutrient digestibility and fecal formation can be promoted [4].…”
Section: Introductionmentioning
confidence: 99%
“…Corn fiber, fruit fibers, rice bran, and whole grains are some of the other fiber sources available for use in pet foods [3]. Full-fat rice bran was tested for palatability and digestibility in pet foods by Pacheco et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…Corn has the highest glycemic index, followed by rice, with barley having the lowest. A low glycemic index is useful for diabetic and obese dogs (9). However, some dogs that could not tolerate β-glucans were observed to have loose or watery stools (1,9).…”
Section: Introductionmentioning
confidence: 99%
“…Murray et al (12) reported that loss of organic matter in vitro was higher in barley than in rice. It has been reported that barley added to dry dog food up to 40% is well tolerated by adult dogs and that complex carbohydrates protect against oxidative stress and cardiovascular disease (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation